A New Spectral Library for Modeling the Surfaces of Hot, Rocky Exoplanets - Kimberly Paragas; Heather A. Knutson; Renyu Hu; Bethany L. Ehlmann; Giulia Alemanno; Jörn Helbert; Alessandro Maturilli; Michael Zhang; Aishwarya Iyer; George Rossman (The Astrophysical Journal)
JWST’s MIRI LRS provides the first opportunity to spectroscopically characterize the surface compositions of close-in terrestrial exoplanets. Models for the bare-rock spectra of these planets often utilize a spectral library from R. Hu et al., which is based on room-temperature reflectance measurements of materials that represent archetypes of rocky planet surfaces. Here we present an expanded library that includes hemispherical reflectance measurements for a greater variety of compositions, varying textures (solid slab, coarsely crushed, and fine powder), as well as high-temperature (500–800 K) emissivity measurements for select samples. We incorporate this new library into version 6.3 of the open-source retrieval package PLATON and use it to show that planetary surfaces with similar compositions can have widely varying albedos and surface temperatures. We additionally demonstrate that changing the texture of a material can significantly alter its albedo, making albedo a poor proxy for surface composition. We identify key spectral features—the 5.6 μ m olivine feature, the transparency feature, the Si-O stretching feature, and the Christiansen feature—that indicate silicate abundance and surface texture. We quantify the number of JWST observations needed to detect these features in the spectrum of the most favorable super-Earth target, LHS 3844 b, and revisit the interpretation of its Spitzer photometry. Lastly, we show that temperature-dependent changes in spectral features are likely undetectable at the precision of current exoplanet observations. Our results illustrate the importance of spectroscopically resolved thermal emission measurements, as distinct from surface albedo constraints, for characterizing the surface compositions of hot, rocky exoplanets.